2022
DOI: 10.1111/2041-210x.13933
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation canopy height estimation in dynamic tropical landscapes with TanDEM‐X supported by GEDI data

Abstract: 1. Vegetation canopy height is a relevant proxy for aboveground biomass, carbon stock, and biodiversity. Wall-to-wall information of canopy height with high spatial resolution and accuracy is not yet available on large scales. For the globally consistent TanDEM-X data, simplifications are necessary to estimate canopy height with semi-empirical models based on polarimetric synthetic aperture radar interferometry (PolInSAR).2. We trained the semi-empirical models with sampled GEDI data, because the assumptions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
(261 reference statements)
0
8
0
Order By: Relevance
“…GEDI provides dense and well distributed lidar waveform measurements across Earths tropical and temperate forests and defines an ideal framework to explore the synergetic use of waveform lidar and interferometric X-band SAR measurements at local to global scales. Indeed, the synergies between TanDEM-X and waveform lidar data [34] have been confirmed by a number of studies using the TanDEM-X / GEDI framework [30][31], [37][38].…”
Section: Introductionmentioning
confidence: 73%
“…GEDI provides dense and well distributed lidar waveform measurements across Earths tropical and temperate forests and defines an ideal framework to explore the synergetic use of waveform lidar and interferometric X-band SAR measurements at local to global scales. Indeed, the synergies between TanDEM-X and waveform lidar data [34] have been confirmed by a number of studies using the TanDEM-X / GEDI framework [30][31], [37][38].…”
Section: Introductionmentioning
confidence: 73%
“…Spaceborne RADAR data offer a complementary source of data, particularly across the tropics. Schlund et al (2022) suggested an approach to combine GEDI data with TanDEM‐X polarimetric SAR data via a semi‐empirical model for canopy height estimations over tropical forests and then validated the results with airborne LiDAR data. A higher and denser vegetation cover was shown to result in larger errors in the estimation of canopy height by the applied linear models.…”
Section: Thematic Groups Being Covered In the Sfmentioning
confidence: 99%
“…1. Stand-, canopy-and tree-level structural analysis by active RS data (Atkins et al, 2023;Blanchard et al, 2023;Coverdale & Davies, 2023;Hardenbol et al, 2022;Schlund et al, 2022;Singh et al, 2023;Tatsumi et al, 2022;Zhang & Liu, 2023).…”
Section: G Ener Al and S Pecific Trendsmentioning
confidence: 99%
See 2 more Smart Citations